Quodvultdeus : a bishop forming Christians in Vandal Africa : a contextual analysis of the pre-baptismal sermons attributed to Quodvultdeus of Carthage - Vopřada, David, (Vigiliae Christianae, Supplements;, 2020)
In Quodvultdeus: a Bishop Forming Christians in Vandal Africa, David Vopřada presents the pre-baptismal catecheses of the fifth-century bishop of Carthage, delivered to the new believers in extremely difficult period of barbaric incursions. Quodvultdeus is generally not appraised as an original philosopher or theologian as his master Augustine was, in this book his qualities of a bishop who was entrusted with the care of his flock come forward. Making interdisciplinary use of the ancient and ecclesiastical history, philosophy, theology, archaeology, exegesis, liturgy science, homiletics, and rhetorics, the book offers a new and most innovative contribution to the life, work, and theology of Quodvultdeus.